Short and practical enantioselective synthesis of linezolid and eperezolid via proline-catalyzed asymmetric alpha-aminooxylation - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of the antibacterials, linezolid (U-100766), and eperezolid (U-100592) using D-proline-catalyzed asymmetric alpha-aminooxylation of aldehydes as the key step is described here. This is the first report on the enantioselective synthesis of linezolid and eperezolid using asymmetric catalysis. (c) 2006 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of (-)-chloramphenicol and (+)-thiamphenicol using tethered aminohydroxylation - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugarn (Tetrahedron, 2006)
An efficient enantioselective synthesis of (-)-chloramphenicol (1) and (+)-thiamphenicol (2) is described. These antibiotics have been synthesized from commercially available 4-nitrobenzaldehyde and 4-(methylthio)benzaldehyde, respectively, using tethered amino-hydroxylation and Sharpless asymmetric epoxidation as the chirality inducing steps. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: asymmetric epoxidation; Asymmetric synthesis; Kinetic resolution; Tethered aminohydroxylation